In vitro anti-biofilm properties of the peel of fruite wall of acorn against Streptococcus mutans - Chavak, Zahra; Mahdian, Nahid; Pakzad, Iraj; Soltani, Mohammad Reza; Badakhsh, Behzad; Ghafourian, Sobhan (German Medical Science GMS Publishing House, 2023)
Dental caries is a multi-factorial infectious disease. The primary cause is dental plaque, a complex of biofilm. It was postulated that the ethanolic extract of fruite wall of acorn may represent a new substance to prevent caries. Hence, the study was performed to evaluate the effect of ethanolic extract of fruite wall of acorn against biofilm formation by , which is associated with dental plaque. The cytotoxicity of the ethanolic extract was determined against Vero cells resulting in an inhibitory concentration of 50 (IC) of 55 µg/ml. After bacterial collection, different concentrations under the IC from the extract were evaluated against biofilm formation of . 3 µg/ml of the extract inhibited the biofilm formation of , and 1 to /ml caused a decrease in and biofilm-production genes. This study showed the potency of the ethanolic extract of fruite wall of acorn against biofilm formation by .